TANTANGAN DAN STRATEGI MERANCANG PROGRAM PENDIDIKAN DAN PELATIHAN BERBASIS KOMPETENSI - Dina Oktapia; Abdul Fattah Nasution; Irma Tussa’diyah Hasibuan; Nur Khotima (Cemara Education and Science, 2024)
This research aims to analyze the challenges and strategies in designing competency-based education and training programs. Analysis of the need for these programs highlights the importance of understanding the complexities of competency-based education and training. The development of competency models is critical in this context because it provides a framework for designing and implementing effective programs. However, implementing competency-based education and training programs actually poses significant challenges, including the need for a deep understanding of the subject matter, the ability to adapt to changing circumstances, and the capacity to integrate theoretical knowledge with practical skills. This study provides insight into strategies that can be used to overcome these challenges and ensure the success of competency-based education and training programs